Creative metaphors in selected models of Nahj al-Balagha Analytic study of semantic constructs (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The procedural approaches for reading a literary text vary in the variety of aspects of creativity in it, and accordingly the critical readings that contribute to illuminating its aesthetics and revealing them according to the recipient's artistic elegance, and the hidden creativity of the rhetorical aspects that the transmitter enriched his literary text, and this is one of these manifestations. It bears a semantic radiance of multiple possibilities, and denotes in depth and clarity the ability of the writer to understand the apparent and hidden links between things and objects, which leads the critic to be experienced in diving into the aesthetics of the simulated image, and to capture its escaped charm, and by taking into account what has been presented, by taking the a loore into account. This Search seeks to read selected models from The simile images contained in the sermons of Nahj al-Balaghah are a vertical reading that seeks to uncover its aesthetic secrets, and its rhetorical connotations, and to clarify as much as possible of their deep meanings contained in their various contexts.